Large‐scale multiplex polymerase chain reaction assay for diagnosis of viral reactivations after allogeneic hematopoietic stem cell transplantation. Issue 8 (6th May 2015) - Inazawa, Natsuko; Hori, Tsukasa; Hatakeyama, Naoki; Yamamoto, Masaki; Yoto, Yuko; Nojima, Masanori; Suzuki, Nobuhiro; Shimizu, Norio; Tsutsumi, Hiroyuki
<x xml:space="preserve">Abstract</x> Viral reactivations following hematopoietic stem cell transplantation are thought to result from the breakdown of both cell‐mediated and humoral immunity. As a result, many viruses could be reactivated individually or simultaneously. Using a multiplex polymerase chain reaction (PCR), we prospectively examined many kinds of viral DNAs at a time in 105 patients who underwent allogeneic hematopoietic stem cell transplantation. In total, 591 whole blood samples were collected weekly from pre‐ to 42 days post‐transplantation and the following 13 viruses were tested; herpes simplex virus 1 (HSV‐1), HSV‐2, varicella‐zoster virus (VZV), Epstein–Barr virus (EBV), cytomegalovirus (CMV), human herpes virus 6 (HHV‐6), HHV‐7, HHV‐8, adenovirus, BK virus (BKV), JC virus (JCV), parvovirus B19, and hepatitis B virus (HBV). Several viral DNAs were detected in 12 patients before hematopoietic stem cell transplantation. The detection rate gradually increased after transplantation and peaked at 21 days. The most frequently detected virus was HHV‐6 (n = 63; 60.0%), followed by EBV (n = 11; 10.5%), CMV (n = 11; 10.5%), and HHV‐7 (n = 9; 8.6%). Adenovirus and HBV were each detected in one patient (1.0%). Detection of HHV‐6 DNA was significantly more common among patients undergoing cord blood transplantation or with steroid treatment. EBV DNA tended to be more common in patients treated with anti‐thymocyte globulin. Multiplex PCR was useful for detecting many viral reactivations after hematopoietic stem cell transplantation, simultaneously. Cord blood transplantation, steroid treatment, or anti‐thymocyte globulin use was confirmed to be risk factors after transplantation. J. Med. Virol. 87:1427–1435, 2015. © 2015 Wiley Periodicals, Inc.